Flash joining of CVD-SiC coated Cf/SiC composites with a Ti interlayer. Issue 13 (October 2017) - Tatarko, Peter; Grasso, Salvatore; Saunders, Theo G.; Casalegno, Valentina; Ferraris, Monica; Reece, Michael J.
Abstract: Flash joining of CVD-SiC coated Cf /SiC samples with a Ti interlayer was achieved using a Spark Plasma Sintering machine. The influence of different heating powers and discharge times were investigated. The sample flash joined at a maximum heating power of 2.2 kW (peak electric current of 370 A) within 7 s showed the highest apparent shear strength of 31.4 MPa, which corresponds to the interlaminar shear strength of the composites. A maximum joining temperature of ∼1237 °C was reached during the flash joining. An extremely rapid heating rate of 9600 °C/min combined with a very short processing time hindered any reaction between the CVD-SiC coating and the Ti interlayer. The formation of a metallic joint (Ti based) in the absence of any detectable reaction phase is proposed as a new joining mechanism. For a conventionally joined SPS sample, the formation of titanium silicide phases inhibited the formation of a bond.